2007
DOI: 10.1111/j.1753-6405.2007.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates for cervical abnormalities in Vanuatu

Abstract: Objective: To use the Pap smear to establish a recent prevalence of cervical abnormalities within a select population in Vanuatu, a developing country. Methods: Cervical smears (n=907) were collected from Ni‐Vanuatu women from both urban and rural islands within Vanuatu between August 2001 and September 2005. Results: The prevalence of low‐grade epithelial abnormalities for the total population was 2.9% and the prevalence of the high‐grade epithelial abnormalities/cancer was 2.0%. There was a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The significant proportion of “other cancers” reported in Vanuatu adults is attributable, at least in part, to a prominence of thyroid cancer which is consistent with published incidence data for Vanuatu, and is not dissimilar to several other Pacific Island populations [ 22 , 23 ]. Previous studies report a higher incidence in Vanuatu of cervical cancer and high-grade epithelial abnormalities (2 %) on screening than Australia [ 24 ], which is consistent with findings that show cervical cancer as an important CoD in adult females. Screening is, however, very limited, and human papillomavirus (HPV) vaccine, which would benefit future generations of women, is not yet generally available.…”
Section: Discussionsupporting
confidence: 88%
“…The significant proportion of “other cancers” reported in Vanuatu adults is attributable, at least in part, to a prominence of thyroid cancer which is consistent with published incidence data for Vanuatu, and is not dissimilar to several other Pacific Island populations [ 22 , 23 ]. Previous studies report a higher incidence in Vanuatu of cervical cancer and high-grade epithelial abnormalities (2 %) on screening than Australia [ 24 ], which is consistent with findings that show cervical cancer as an important CoD in adult females. Screening is, however, very limited, and human papillomavirus (HPV) vaccine, which would benefit future generations of women, is not yet generally available.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies also report a higher incidence of cervical cancer and high-grade epithelial abnormalities (2.0%) on screening than Australia (349), which is consistent with findings here that show cervical cancer as an important CoD in adult females. Screening is however very limited.…”
Section: As Vanuatu Continues To Improve Data Collection and Further supporting
confidence: 92%
“…There has been a three-fold increase in the rate of highgrade cervical abnormalities over a 10-year period between two Vanuatu pap smear studies. 4,5 Similarly, Fotinatos et al reported a high-grade cervical abnormality rate of 2.0% that was more than three times the rate reported by the Victorian Cervical Cancer Registry (0.62%) during the same time period. 6 The main health centre in Vanuatu is located on Efate Island (Vila Central Hospital), with smaller medical facilities on the islands of Tanna, Ambae and Espiritu Santo (Luganville).…”
Section: Introductionmentioning
confidence: 89%